Axial length and its associations in the Ural Very Old Study - Bikbov, Mukharram M.; Kazakbaeva, Gyulli M.; Rakhimova, Ellina M.; Rusakova, Iuliia A.; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Panda-Jonas, Songhomitra; Gilmanshin, Timur R.; Zainullin, Rinat M.; Bolshakova, Natalia I.; Safiullina, Kamilia R.; Gizzatov, Ainur V.; et al. (Scientific reports, 2021)
To assess the distribution of axial length as surrogate for myopia and its determinants in an old population, we performed the Ural Very Old Study as a population-based cohort study. Out of 1882 eligible individuals aged 85 + years, the Ural Very Old Study performed in an urban and rural region in Bashkortostan/Russia included 1526 (81.1%) individuals undergoing ophthalmological and medical examinations with sonographic axial length measurement. Biometric data were available for 717 (47.0%) individuals with a mean age of 88.0 ± 2.6 years (range 85–98 years; 25%). Mean axial length was 23.1 ± 1.1 mm (range 19.37–28.89 mm). Prevalences of moderate myopia (axial length 24.5–< 26.5 mm) and high myopia (axial length ≥ 26.5 mm) were 47/717 (6.6%; 95% CI 4.7, 8.4) and 10/717 (1.4%; 95% CI 0.5, 2.3), respectively. In multivariable analysis, longer axial length was associated (coefficient of determination r 2 0.25) with taller body height (standardized regression coefficient beta:0.16;non-standardized regression coefficient B: 0.02; 95% confidence interval (CI) 0.01, 0.03; P < 0.001), higher level of education (beta: 0.12; B: 0.07; 95% CI 0.02, 0.11; P = 0.002), and lower corneal refractive power (beta: − 0.35; B: − 0.23; 95% CI − 0.28, − 0.18; P < 0.001). Higher prevalence of moderate myopia, however not of high myopia, was associated with higher educational level (OR 1.39; 95% CI 1.09, 1.68; P = 0.007) and lower corneal refractive power (OR 0.77; 95% CI 0.63, 0.94; P = 0.01). In this old study population, prevalence of moderate axial myopia (6.6% versus 9.7%) was lower than, and prevalence of high axial myopia (1.4% versus 1.4%) was similar as, in a corresponding study on a younger population from the same Russian region. Both myopia prevalence rates were higher than in rural Central India (1.5% and 0.4%, respectively). As in other, younger, populations, axial length and moderate myopia prevalence increased with higher educational level, while high myopia prevalence was independent of the educational level.